eLearning in Physical Therapy: Lessons Learned from Transitioning a Professional Education Program to Full eLearning during the COVID-19 Pandemic - Ng, Leo; Seow, Kuang Cheng; Macdonald, Laetitia; Correia, Christina; Reubenson, Alan; Gardner, Peter; Spence, Angela; Bunzli, S.; De Oliveira, Beatriz I.R. (OXFORD UNIV PRESS INC, 2021)
Objective: The objectives of this cross-sectional qualitative study were to explore the perspectives of students enrolled in one physical therapist undergraduate education program in Australia about their experience with transitioning to full eLearning and student recommendations to improve the learning experience during the COVID-19 pandemic.